2008
DOI: 10.1063/1.2831917
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio calculation of carbon clusters. II. Relative stabilities of fullerene and nonfullerene C24

Abstract: Chemical stabilities of six low-energy isomers of C 24 derived from global-minimum search are investigated. The six isomers include one classical fullerene ͑isomer 1͒ whose cage is composed of only five-and six-membered rings ͑5 / 6-MRs͒, three nonclassical fullerene structures whose cages contain at least one four-membered ring ͑4-MR͒, one plate, and one monocyclic ring. Chemical and electronic properties of the six C 24 isomers are calculated based on a density-functional theory method ͑hybrid PBE1PBE functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
30
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 72 publications
6
30
0
1
Order By: Relevance
“…For coronene, the theoretically calculated energies vary from 7.02 eV for C 24 H 12 to 8.25 eV for C 24 . This last value also agrees with the calculations of An et al (2008) for C 24 . The decrease of the IP with hydrogenation has also been reported for anthracene (C 14 H 10 ) and naphthalene (C 10 H 8 ) first dehydrogenated and first superhydrogenated states, where ∆IP becomes more constant as the PAH gets larger (Kapinus 2004).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…For coronene, the theoretically calculated energies vary from 7.02 eV for C 24 H 12 to 8.25 eV for C 24 . This last value also agrees with the calculations of An et al (2008) for C 24 . The decrease of the IP with hydrogenation has also been reported for anthracene (C 14 H 10 ) and naphthalene (C 10 H 8 ) first dehydrogenated and first superhydrogenated states, where ∆IP becomes more constant as the PAH gets larger (Kapinus 2004).…”
Section: Discussionsupporting
confidence: 81%
“…An et al (2008) reports an EA of 1.89 eV for C 24 , which agrees with the ∼0.1 eV variation per dehydrogenation derived from the IPs. Therefore, we also consider the relation given by Eq.…”
Section: Ionization Potentials and Electron Affinitiessupporting
confidence: 76%
“…In fact, as noted earlier, some isomers with one or two squares are favoured over classical cages for C 24 and C 26 [18,19]; by extension it might be expected that a favoured square-containing isomer would be more likely for C 58 than the larger C 62 .…”
Section: Structural Nepotismmentioning
confidence: 63%
“…Previous studies have suggested that energies of carbon cages rise rapidly with the numbers of both sub-hexagonal [18,19] and larger [20] faces.…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation